2013
DOI: 10.5012/bkcs.2013.34.1.139
|View full text |Cite
|
Sign up to set email alerts
|

Integration of Headspace Solid Phase Micro-Extraction with Gas Chromatography for Quantitative Analysis of Formaldehyde

Abstract: A study was carried out to evaluate the solid phase micro-extraction (SPME) for formaldehyde emission analysis of uncoated plywood. In SPME, formaldehyde was on-fiber derivatized through headspace extraction and analyzed by gas chromatography coupled with mass spectrometry (GC/MS). The SPME was compared with desiccators (DC-JAS 233), small-scale chamber (SSC-ASTM D6007) and liquid-liquid extraction (LLE-EPA 556) methods which were performed in accordance with their respective standards. Compared to SSC (RSD 4.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 17 publications
1
6
0
Order By: Relevance
“…The first attempts at GC-MS analysis of unreacted formaldehyde were in good accordance with earlier studies, [17][18][19] and indicated the need for derivatization. The reaction that forms formaldehyde-DNPH is shown in Scheme 1.…”
Section: Resultssupporting
confidence: 81%
See 2 more Smart Citations
“…The first attempts at GC-MS analysis of unreacted formaldehyde were in good accordance with earlier studies, [17][18][19] and indicated the need for derivatization. The reaction that forms formaldehyde-DNPH is shown in Scheme 1.…”
Section: Resultssupporting
confidence: 81%
“…High performance liquid chromatography (HPLC) is the most widely applied method for the determination of formaldehyde. Gas chromatography coupled to mass spectrometry (GC‐MS) is a versatile analytical technique and attempts have been made to apply GC‐MS to the determination of formaldehyde with limited success . Unfortunately, the thermal instability makes direct quantification of formaldehyde by GC‐MS difficult and the method is therefore prone to robustness issues.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The products of FA derivatization are usually recovered using liquid–liquid [ 55 ] or liquid–solid phase extraction methods [ 56 ], but these procedures greatly complicate the analysis. Therefore solid-phase microextraction (SPME) is the most convenient approach [ 57 , 58 ]. There are several approaches based on the joint usage of extraction and derivatization: the reaction could be performed in the working solution using headspace or liquid SPME [ 59 ] as well as derivatization on fiber [ 60 ].…”
Section: In Vitro Fa Measurementmentioning
confidence: 99%
“…As a result, microextraction techniques have been extensively developed but not widely applied to cosmetic samples [17]. Solid-phase microextraction (SPME) has been combined with GC to measure various analytes in extracts from cosmetic samples [18]. Using SPME to measure cosmetic fragrance does not always give quantitative results [19].…”
Section: Introductionmentioning
confidence: 99%